Hukuman Bagi Pelaku Seks Komersial - Eriyani Mendrofa; Sumiyati Sumiyati (Sekolah Tinggi Teologi Jaffray Jakarta, 2020)
The issue of punishment for commercial sex offenders continues to be debated both in social, psychological, and legal aspects. Through this paper, the author presents a conceptual analysis related to the issue. For the writer, the punishment for commercial sex workers is not right. The author proposes a more human approach to refer to Jesus' actions. This coaching is expected to be more inclined to positive personal recovery from a woman or man who is a former commercial sex offender.